Transdisciplinary insight of digital architecture - Correia, R. M. (2018)
The research outlines a historic perspective of transdisciplinary digital architecture through the work of key personalities by establishing links between them. Researches on digital architecture history are generally grounded on methods with limited sets of primary sources and data is lost. Following the increasing availability of digital data sources in the internet, which were not created and structured with research purposes in mind, new methods are required for mapping, analyzing and visualizing it. Data-driven and geospatial approaches can allow researchers to address multidimensional aspects and facts. This paper presents the first preliminary results of an ongoing research.